f(x)= 3x – 4×2 +6x and g(x)= 5x +2×2 – 3x. What is f(x) g(x)? A)-2x – 6x² +9x B)- 2x² – 6x² – 3x C)2x²+6x²+32

Question

f(x)= 3x – 4×2 +6x and g(x)= 5x +2×2 – 3x. What is f(x) g(x)?

A)-2x – 6x² +9x
B)- 2x² – 6x² – 3x
C)2x²+6x²+32
D)8×2 – 6×2-9x

in progress 0
Melanie 1 week 2021-11-20T11:36:52+00:00 1 Answer 0 views 0

Answers ( )

    0
    2021-11-20T11:38:27+00:00

    f(x)g(x) = 9x² + 10x – 16

    Step-by-step explanation:

    Step 1:

    Given f(x) = 3x – 4 × 2 + 6x and g(x) = 5x + 2 × 2 – 3x

    f(x) = 9x – 8

    g(x) = 2x + 4

    f(x)g(x) = (9x – 8)(2x + 4)

    = 18x² + 36x – 16x -32

    = 18x² + 20x – 32

    = 9x² + 10x – 16

Leave an answer

45:7+7-4:2-5:5*4+35:2 =? ( )